Effects of standardized ileal digestible tryptophan:lysine ratio on growth performance and economics of 25- to 45-lb nursery pigs - Marcio Antonio Dornelles Goncalves; Michael D Tokach; Steven S Dritz; K J Touchette; Nora M Bello; Robert D Goodband; Joel M DeRouchey; Jason C Woodworth (Kansas Agricultural Experiment Station Research Reports, 2014)
The use of feed-grade tryptophan (Trp) in swine diets has become more economical recently due to the increased cost of soybean meal and the increased usage of dried distillers grains with solubles (DDGS). Therefore, the objectives of this study were to estimate the effects of the standardized ileal digestible (SID) tryptophan:lysine (Trp:Lys) ratio on growth performance and economics of 25- to 45-lb nursery pigs housed in a commercial environment. A total of 1,088 pigs (PIC 337 × 1050; initially 24.8 ± 1.2 lb BW) were used in a 21-d growth trial. Pigs were weaned at 16 d of age and grouped into pens of 27 pigs (14 gilts and 13 barrows). Pigs were fed common diets until d 28 after weaning. On d 28, pens of pigs were weighed and blocked by average BW, then randomly assigned to 1 of 7 dietary treatments in a randomized complete block design with 6 pens per treatment. Dietary treatments contained 30% DDGS and were 14.5, 16.5, 18.0, 19.5, 21.0, 22.5, and 24.5% SID Trp:Lys ratio. The SID Trp:Lys ratio was increased by adding crystalline L-Trp to the control diet at the expense of corn. The SID Lys requirement was 1.07% and was reduced by 0.10 percentage points below the estimated requirement to ensure that lysine was the second limiting amino acid throughout the experiment. Increasing SID Trp:Lys ratio increased (quadratic, P<0.002) ADG, ADFI, and final BW through the 21.0% SID Trp:Lys ratio with no change thereafter. Consequently, F/G, caloric efficiency, and income over feed cost (IOFC) also improved as the SID Trp:Lys ratio increased from 14.5 to 21.0% of Lys. For ADG, pigs fed the 18% SID Trp:Lys ratio were at 97% of maximum response, whereas for IOFC, pigs fed 18% SID Trp:Lys were at 98% of the maximum. Risk of reduced performance and profitability was much greater when SID Trp:Lys was formulated below 18% than when formulated above 18%. In conclusion, formulating nursery diets below 18% SID Trp:Lys reduced feed intake and, consequently, growth performance.; Swine Day, Manhattan, KS, November 20, 2014
Keywords: Swine Day; 2014; Kansas Agricultural Experiment Station contribution; no. 15-155-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1110; Amino acid ratio; Economics; Nursery pig; Tryptophan